Face-To-Face Learning Methods Are Limited in Overcoming Students' Learning Difficulties During The Pandemic Covid-19 - Prasetyo, Yoyok; Irvan Sir; Atmam Amir (ETDC: Indonesian Journal of Research and Educational Review, 2022)
In Indonesia, the impact of the pandemic was quite severe. This is evidenced by the high mortality rate. To reduce its spread, the minister of education and the government imposed an online learning system which was found to be less effective at elementary school levels, especially in physical education and health lessons, which required a lot of physical activity. Various obstacles that occurred in the learning model in the network resulted in educators preferring the limited face-to-face learning model as a means of delivering material to students. Despite the great risk, it turns out that this limited face-to-face learning model is more effectively used than other learning models. To reduce risk, health protocols must be carried out before starting learning. The results of this limited face-to-face learning show an increase in students' understanding of the material at MI Maarif NU Kebalandono. As a suggestion, a professional teacher must also be able to adapt and adjust to the learning they will do in class under any conditions so that the competencies expected in the curriculum can be conveyed properly to students.